Water deprivation-induced sodium appetite - De Luca, Laurival A. [UNESP]; Pereira-Derderian, Daniela T. B. [UNESP]; Vendramini, Regina C. [UNESP]; David, Richard B. [UNESP]; Menani, José Vanderlei [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
A water deprived animal that ingests only water efficiently corrects its intracellular dehydration, but remains hypovolemic, in negative sodium balance, and with high plasma renin activity and angiotensin II. Therefore, it is not surprising that it also ingests sodium. However, separation between thirst and sodium appetite is necessary to use water deprivation as a method to understand the mechanisms subserving sodium appetite. For this purpose, we may use the water deprivation-partial repletion protocol, or WD-PR. This protocol allows performing a sodium appetite test after the rat has quenched its thirst; thus, the sodium intake during this test cannot be confounded with a response to thirst. This is confirmed by hedonic shift and selective ingestion of sodium solutions in the sodium appetite test that follows a WD-PR. The separation between thirst and sodium appetite induced by water deprivation permits the identification of brain states associated with sodium intake in the appetite test. One of these states relates to the activation of angiotensin II All receptors. Other states relate to cell activity in key areas, e.g. subfornical organ and central amygdala, as revealed by immediate early gene c-Fos immunoreactivity or focal lesions. Angiotensin II apparently sensitizes the brain of the water deprived rat to produce an enhanced sodium intake, as that expressed by spontaneously hypertensive and by young normotensive rat. The enhancement in sodium intake produced by history of water deprivation is perhaps a clue to understand the putative salt addiction in humans.The paper represents an invited review by a symposium, award winner or keynote speaker at the Society for the Study of Ingestive Behavior [SSIB] Annual Meeting in Portland, July 2009. (C) 2010 Published by Elsevier B.V.
Keywords: Sodium intake; Thirst; Motivation; Dehydration; Sensitization; Hypertension